Variation in Laying Traits of Hortobagy White Breeder Geese by Year and Age - Toth, Peter; Janan, Janbaz; Nikodemusz , Etelka (International Journal of Poultry Science, 2014)
Daily egg production data for four breeder flocks of Hortobagy White geese recorded in 2012 and 2013 were analyzed. Flock age ranged from one to five years. The flock size differed considerably within and between years. The flocks were formed one month before the laying period and housed separately in sheds with deep litter system and yard access and given a granulated laying feed throughout the laying period. They were maintained under natural daylight, air temperature and relative air humidity. The laying traits analyzed per flock per week were the number of eggs per goose and laying intensity related to the number of surviving geese. The onset of egg laying differed by year and age: in 2013 it occurred three weeks and four weeks earlier in the one-year old and elder flocks, respectively, than in 2012. With one-year old flocks, the laying period lasted for 15 weeks in 2013 and for 18 weeks in 2012, with the elder flocks it lasted for 20 and 21 weeks, respectively. The laying traits also differed by year but generally improved with the age, irrespective of the year. Geese produced 28-35 eggs in their first year of lay, 45-56 eggs in their second year, 51-42 eggs in their third and fourth years and 43-45 eggs in their fifth years. The laying intensity was 27-28% in the first year, 31-40% in the second year, 36-29% in the third and fourth year and 30-32% in the fifth year.